ICT-Based Learning Management at Al-Hikmah Integrated Islamic High School, Maros District - Arifin, Nurqarirah; Hasan, Mardhiah; Syamsuddin, Syamsuddin; Nirmayanthi, Andi; Aliman, Aliman; Semi, Hijar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study is motivated by the importance of technology-based learning management in the digital era, which presents challenges for schools in integrating ICT. The aim of this research is to analyze the planning, implementation, and evaluation of technology-based learning management at SMAS Islam Terpadu Al-Hikmah Maros Regency. This research uses a descriptive qualitative approach to illustrate the application of technology-based learning management at the school. Data were collected through observations, interviews, and documentation involving school principals, vice principals, teachers, staff, and students. The data were analyzed through reduction, presentation, and conclusion drawing. The results show that planning is conducted by identifying technological needs, planning learning strategies that integrate ICT, and developing ICT infrastructure, including devices and networks. Implementation involves infrastructure, using digital platforms, and providing training teachers to optimize technology in learning, including ICT-based exams. Evaluation is carried out through classroom observations, analysis of student learning outcomes, and evaluation meetings to gather feedback and formulate follow-up actions. In conclusion, this study contributes to the development of ICT-based education management, with the implication that school principals need to support technology development and training for educators, educators must be creative in using ICT, students need to be more independent, and parents are expected to support by providing devices and participating in school activities.